ASPECTOS DETERMINANTES EN LA INTERNACIONALIZACIÓN DE LA EMPRESA FAMILIAR - Rubén Fernández Ortiz; Manuel Carlos Vallejo Martos; Guadalupe Fuentes Lombardo (Revista de Estudios Empresariales. Segunda Época, 2007)
Internationalization strategy is an important decision for both family and non family firms.Some singularities of family firms, pointed out by literature as strengths and weaknesses, can have influence on the success or failure of their international expansion. Results of our research, conducted in a guarantee of origin and quality of a wine industry in Spain, show that there is a clear link among familiness, weaknesses and strengths and international strategy.Higher levels of familiness involve more difficulties to international growth because family firms show most of the standard weeknesses and very few strengths. Lower levels of familiness involve less problems to international expansion because weaknesses don’t exist hardly and they show most of strengths.